Development of Wireless Data Transfer System on Unmanned Underwater Vehicles Application - Mohd Aras, Mohd Shahrieel; Abdul Azis, Fadilah; Fara Ashikin , Ali; Muhammad Nur , Othman (2013)
This paper presents the development of wireless system for data transfer on unmanned underwater vehicles (UUV) using Xbee Pro 60mWatt. Nowadays, wireless communication technology has become part of our daily life. However, research in underwater wireless communication has been active to design the methods for wireless data transmission underwater. In this system is very important to transfer data from UUV to vessel/platform or other UUV. The technology of underwater wireless communication can be used such as to detect fish or ship, identify the environment at bottom of sea and transmitting data from sea to land. Throughout this project, a few experiments have been done to develop a wireless system for data transfer from underwater vehicles to Computer based (CB). A transmitter (CB) will send a data to a receiver (UUV) that attached to a UUV (FKE-UTeRGlider). Hardware’s that has been used such as XBee Pro 60mW Antenna and XBee Pro Starter Kit that will function as a transmitter and receiver to transfer data using wireless systems respectively. The microcontroller used in this project is PIC microcontroller that functions as an interface with the computer. Graphical User Interface (GUI) by Visual Basic (VB) software has been used as a way to communicate with the PIC. All the results for data transfer will discuss in this paper